RESEARCH ON SOLUTION METHOD OF CONTACT STIFFNESS OF CURVIC COUPLINGS CONSIDERING TOOTH SURFACE ROUGHNESS - MA Wu; WANG AiLun; WANG Hai; YANG ZhengLie (Jixie qiangdu)
Aiming at the problem that the contact stiffness analysis method of curvic couplings can not consider the contact interface microscopic morphology,an analytical model of the contact interface stiffness was proposed.Through the stress analysis and stiffness transformation,the general model of curvic couplings contact interface stiffness was obtained,and the GW rough surface model was brought into it to obtain the specific curvic couplings contact interface stiffness formula based on the GW rough surface model.Finally,the analytical model results were compared with finite element results.The effect of surface topography on the contact stiffness of curvic couplings was obtained,and the relationship between the normal contact stiffness and the tangential contact stiffness with the preload and tangential force were obtained.The research shows that the analytical model matches well with the finite element results,which proves the rationality of the analytical model and provides a theoretical reference for the preload force and torque design of the rotors with curvic couplings.